Comparison between thyroid stimulating immunoglobulin and TSH-receptor antibodies in the diagnosis and management of Graves’ disease - Yao, Peiwei; Xie, Yunliang; Wang, Yunlin; Liang, Chunyan; Huang, Bingwen (Frontiers in Endocrinology, 2024)
TSH-receptor antibodies (TRAb) directed against the TSH receptor (TSH-R) induce hyperthyroidism in patients with Graves′ disease (GD). TRAb detected by previous radioimmunoassay only reflects the presence of autoantibodies, but not the function of such antibodies. Thyroid stimulating immunoglobulins (TSI) is a relatively new method for assessing TSH-receptor antibodies function. The aim of this study was to investigate the role of TSI in the diagnosis and management of GD.